Toward the Abe statement on the 70th anniversary of the end of World War II lessons from the 20th century and a vision for the 21st century for Japan - Cannon, Tara; 21-Seiki K?os?o Kondankai; Advisory Panel on the History of the 20th Century and on Japan's Role and the World ‪Order in the 21st Century (2017)
"In 1955 and 2005, Japan's prime ministers released landmark statements to mark the 50th and 60th anniversaries of the end of World War II. Many around Asia and the world were focused on what sort of statement Prime Minister Abe Shinzo would release. The media was filled with speculation about whether his statement would uphold previous prime ministers' statements and include words such as "aggression," "colonial rule," or "apology." It was in this context that Prime Minister Abe himself commissioned a panel of Japan's foremost experts to look back on the 20th century and the path Japan followed before and after the war, and look ahead to the role Japan should play in the 21st century. This book brings together the presentations and commentary by the panel members as they explore Japan in the 20th century, lessons to be drawn from Japan's experience, its reconciliation with both Western and Asia countries, and the contributions Japan should make to the world going forward"--Publisher's website.
Preface / by Taizo Nishimuro -- Introduction: toward the Abe Statement on the 70th anniversary of the end of World War II -- How should we view the path the world and Japan took during the 20th century? What are lessons we should draw from the experiences in the 20th century? -- What is the path that Japan has taken in the 70 years since the war's send in light of the lessons learned from the 20th century? In particular, how should the commitment to peace, economic development and international contributions by postwar Japan be evaluated? -- Seventy years of reconciliation with the United States, Australia, and Europe -- Seventy years of reconciliation within China, the Republic of Korea, and other Asian countries -- What is our vision of Asia and the world of the 21st century, drawing on the lessons learned from the 20th century? What are the contributions that Japan should make? What are the specific measures that Japan should take on the occasion of the 70th anniversary of the end of World War II?
"Originally published in Japanese under the title of Sengo 70 nen danwa no ronten, by Nikkei Publishing Inc. in 2015"--Title page verso.
Includes bibliographical references.
Japan Foundation
Translated from the original Japanese into English.
Keywords: Japan -- History -- 1945-.; Japan -- Foreign relations -- 1945-.; Japan -- Economic conditions -- 1989-.